Dynamic replication to reduce access latency based on fuzzy logic system. (May 2017) - Wang, Tao; Yao, Shihong; Xu, Zhengquan; Pan, Shaoming
Highlights: The model of access latency optimization rectifies the lack of theoretical analysis on the replications and the data access latency reduction. FLSDR always selects the optimal replica and places replicas onto the optimal node. FLSDR uses a fuzzy logic system to realize the accurate and prudent replica replacement. Graphical abstract: Abstract: In a distributed environment, limited available bandwidth resources lead a high data access latency. Replication is a popular method that can upgrade the access performance and increase the data availability. However, unreasonable replication would cause over-consumption of system resources and finally a further deterioration on data access latency. So, In this paper, a theoretical model of access latency optimization with replication is presented firstly, which complement the blank space, and then a well-designed dynamic replication strategy is proposed, which consists of three algorithms: replica selection algorithm, replica layout algorithm and replica replacement algorithm. Replica selection algorithm selects the optimal replica with a hierarchical time cost based on the derivation of the theoretical model. Replica layout algorithm selects the optimal node for placing the replica based on the spatio-temporal locality of data access. Replica replacement algorithm, in which the fuzzy logic system is introduced originally, deletes replica when the available storage space is insufficient. FLSDR is tested by OptorSim and experimental results show that FLSDR achieves better performance in comparison with other algorithms in terms of mean job execution time, computing resource usage, number of data scheduling between clusters and number of replicas.